Clinical analysis of percutaneous endoscopic unilateral laminotomy for bilateral decompression for single segment degenerative lumbar spinal stenosis: a systematic review and single-arm meta-analysis - Jiang, Tianqi; Chen, Zhijun; Luo, Yitong; Tian, Xinyue; Zhou, Yanni; Huan, Yanqiang; He, Yongxiong (Frontiers in Surgery, 2025)
BackgroundIn recent years, percutaneous endoscopic unilateral laminotomy for bilateral decompression (PE-ULBD) has been used to treat degenerative lumbar spinal stenosis (LSS) and has achieved good results. Some researchers have conducted statistical analysies and evaluated the efficacy of this technology. In this systematic review and single-arm meta-analysis, the effectiveness of PE-ULBD as a surgical method for treating single segment LSS was evaluated from the perspective of evidence-based medicine. The aim was to provide a scientific basis for the clinical application of this technology in LSS treatment.MethodsA systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 396 studies published before May 29, 2024 were collected from the PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure(CNKI), and WanFang databases.ResultsEight retrospective studies were found with 287 patients who met the inclusion criteria set for the systematic review and single-arm meta-analysis. We used the methodological index for non-randomized studies (MINORS) scale to evaluate the quality of the included studies. The results indicated that significant difference in VAS scores between preoperative and postoperative back and leg pain and the difference between the control results recorded before and after the two types of pain scores was statistically significant (P < 0.05). In addition, the difference between the Oswestry Disability Index (ODI) scores recorded in the different groups before and after surgery was statistically significant (P < 0.05). Although the results showed high heterogeneity, a sensitivity analysis showed that there was no significant deviation in other results except for the VAS and ODI score for leg pain in the preoperative and three-month postoperative groups. Secondary clinical outcomes included an average operational time of 97.15 min (95% CI = 82.83, 111.47), an average intraoperative bleeding volume of 26.52 ml (95% CI = 10.51, 42.52), an average hospital stay of 4.16 days (95% CI = 2.96, 5.35), and an incidence of complications of 0.10 (95% CI = 0.06, 0.14).ConclusionOur results indicate that the PE-ULBD technique has significant short and long-term clinical efficacy for the treatment of single-segment LSS and is worthy of clinical application and promotion.